The good, the bad and the irritating a practical approach for parents of children who are attention seeking - Mellor, Nigel; Thir.; Sage eBooks (Bristol : Lucky Duck, 2000)
What is the pattern behind the bewildering variety of misbehaviour children can display at home? Which explanations for behaviour are not helpful? This text presents a user-friendly guide to the perplexing problem of attention seeking.
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: Child rearing; Attention-seeking.; Child psychology; Problem children -- Behavior modification; Child care; Electronic books